Estimation of carrageenan concentration by using ultra sonic waves and back propagation neural networks - Prasad, Reddy; Krishnaiah, Duduku; Awang, Bono; Paulraj, Murugesa Pandiyan, Prof. Madya; Rosli, Mohd Yunus; Naveena Lakshmi (Asian Network for Scientific Information, 2011)
Link to publisher's homepage at www.ansinet.com/